A Preliminary Study on the Climate Adaptive Design of Green Rural Houses in west China. (2017) - Liu, Yu; Wang, Jin; Ren, Juan; Xiao, Qiubo; Zhao, Juan
Abstract: This paper introduces a preliminary study on the climate adaptive design of green rural houses in the Qinling mountainous region of west China. Based on literature reviews and field investigations on the existing traditional and contemporary rural houses in the researched region, the folk wisdom implied in the traditional rural houses, the perceptions and expectations of local residents, and the inheritance of folk wisdom in contemporary rural houses, are identified and discussed. Suggestions for the climate adaptive design of new rural houses in the researched region are provided, further researches are also recommended.